Higher Education in Arab Countries: from Past to Present - N. A. Uspenskaya (Vestnik MGIMO-Universiteta)
The article describes the problems of higher education in the Arab countries from the time of caliphate in the 7th century to present time. The Arab caliphate had a number of scientific centres based on the principles of ancient Greek science and culture. The author stresses the role of interpreters and translators in the development of science, preservation and development of the ancient school of knowledge. Many of ancient scientific books appeared in Europe only in Arabic translation. That means that science and education in the Arab countries was mostly based on ancient science. One of great problems of education in the Arab countries is the recession of its quality and backwardness as compared to European education. The reason is lack of finances and unstable situation in the region. The author illustrates the article with the situation in educational institutions of Egypt. Egypt has one of the oldest and most individual systems of education in the Arab countries. The article shows secular universities as well as one of the most influential religion universities, Al-Azhar. Today, religion education in oriental countries is gaining more and more importance. Religion penetrates all spheres of society. The financial streams in the Arab countries are controlled by Muslim circles.